(untitled) (Indian Journal of Animal Production and Management, 2013)
Season of birth and age at sexual maturity had a non-significant effect on first lactation milk yield. The overall least-squares mean lactation milk yield was 2154.07 ± 16.88 liters (Lt). Significant effect of batch was found on first lactation milk yield in the present study. Cows belonging to 4th batch recorded significantly (P<0.0) higher lactation milk yield (Lt) of 2475.93 ± 19.65. The effects of season of birth and age at sexual maturity were found to have non-significant effect on lactation length. The overall least-squares mean value for lactation length was 300.16 ± 0.06 days.